1996
DOI: 10.1016/0014-5793(96)01017-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase activity in heart cells

Abstract: the activation of 15-LOX in the heart tissue of rabbits by Abstract Arachidonic acid (AA) metabolism via the lipoxygenase (LOX) pathway in rat hearts and in cultured rat hypercholesterolemia [7]. cardiomyocytes was investigated using 1-[14C]AA. LOX activityWe describe here the presence of 12-LOX activity in rat was detected in the mierosomal fraction, in the high speed heart muscle and in cultured rat cardiomyocytes. supernatant prepared from rat hearts and in rat eardiomyocyte supernatant. LOX products from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…A 12−LO isoform has been cloned from cardiac muscle [13] and 12−HETE, the product of 12/15−LO, has been found to be the main LO metabolite in ventricular cardiomyocytes [14]. Our laboratory previously demonstrated the possible involve− ment of 12−HETE in cardiac glucose transport [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A 12−LO isoform has been cloned from cardiac muscle [13] and 12−HETE, the product of 12/15−LO, has been found to be the main LO metabolite in ventricular cardiomyocytes [14]. Our laboratory previously demonstrated the possible involve− ment of 12−HETE in cardiac glucose transport [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the biological function and significance of the different LO isoforms have remained unclear 5. 12‐LO was found to be expressed in the heart1 and 12( S )‐HETE represents the main LO metabolite in ventricular cardiomyocytes 6…”
Section: Introductionmentioning
confidence: 99%
“…5 was found to be expressed in the heart 1 and 12(S)-HETE represents the main LO metabolite in ventricular cardiomyocytes. 6 Interestingly, 12(S)-HETE induces the phosphorylation of actin fibers, leading to an increased actin filament content and enhancement of actin polymerization. 7,8 Involvement of PKC in this process has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it has been reported that 12(S)-HETE induces the phosphorylation of major cytoskeletal proteins, like actin, specifically leading to an increased actin filament content and an enhancement of actin polymerization. Breitbart and co-workers [16] first reported the presence of 12-LO activity in rat ventricular cardiomyocytes, with enzyme activity being detected in both the cytosol and microsomal fractions. Consistent with these findings, our confocal data presented here confirm that immunofluorescence specific for actin and 12-LO could be detected in ventricular cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of certain mammalian LO isoforms (5-, 12-or 15-LO) have been identified in various tissues [13,14], but, for most of them, the biological function and significance remain unclear [12,14,15]. Sigal and co-workers [13] have cloned and characterized a 12-LO isoform from cardiac muscle, and 12(S)-HETE was found to be the main LO metabolite in ventricular cardiomyocytes [16]. This isoform has also been described in a variety of rat, mouse and human tissues [17].…”
Section: Introductionmentioning
confidence: 99%